Undetectable high-sensitivity troponin in combination with clinical assessment for risk stratification of patients with chest pain and normal troponin at hospital arrival. Issue 6 (September 2020) - Sanchis, Juan; Valero, Ernesto; García Blas, Sergio; Barba, Esther; Pernias, Vicente; Miñana, Gema; Brasó, José; Fernandez-Cisnal, Agustín; Gonzalez, Jessika; Noceda, José; Carratalá, Arturo; Chorro, Francisco J; et al.
Background: Undetectable high-sensitivity cardiac troponin (hs-cTn) in a single determination upon admission may rule out acute coronary syndrome. We investigated undetectable hs-cTnT (<detection limit; <5 ng/l) together with clinical risk scores (GRACE, TIMI, HEART and a previously published simple score), for one-year outcomes in patients with chest pain and normal hs-cTnT (<99th percentile; <14 ng/l) upon admission. Methods: This study was a retrospective design involving 2254 consecutive patients (July 2016–November 2017). The primary endpoint was one-year death or acute myocardial infarction; the secondary endpoint added unstable angina requiring revascularization. Early (<90 minutes since pain onset, n = 661) and late ( n = 1593) presenters were separately considered. Results: A total of 56 (2.5%) patients reached the primary endpoint and 91 (4%) the secondary endpoint. Undetectable hs-cTnT had a poor C-statistic in early and late presenters (0.648 and 0.703, respectively). Adding hs-cTnT measurable concentrations above the detection limit (as continuous variable) significantly enhanced the C-statistics (0.754 and 0.847, respectively). Addition of the HEART (0.809, p = 0.005) or simple clinical scores (0.804, p = 0.02) further improved the model and significantly reclassified patient risk, in early presenters. The results were similar for the secondary endpoint. The TIMI risk score performed worse and the GRACE score did not give additional information. In late presenters, no clinical score provided significant additional information over hs-cTnT. Conclusions: Diagnostic algorithms should consider not only whether hs-cTnT is above or below the detection limit but also its concentration if above, for risk stratification over one year in patients with initial normal hs-cTnT. The clinical scores provide valuable additional information in early presenters.